Gold-catalyzed cycloisomerization of 1,6,8-dienyne carbonates and esters to cis-cyclohepta-4,8-diene-fused pyrrolidines - Sally (2014)
A synthetic approach that provides access to cis-cyclohepta-4,8-diene-fused pyrrolidines efficiently through AuI-catalyzed cycloisomerization of 1,6,8-dienyne carbonates and esters at a low catalyst loading of 2 mol % is reported. Starting carbonates and esters with a pendant alkyl group on the terminal alkenyl carbon center were found to favor tandem 1,2-acyloxy migration/cyclopropanation followed by Cope rearrangement of the resulting cis-3-azabicyclo[3.1.0]hexane intermediate. On the other hand, substrates containing a terminal diene or starting materials in which the distal alkene moiety bears a phenyl substituent were observed to undergo competitive but reversible 1,3-acyloxy migration prior to the nitrogen-containing bicyclic ring formation. The delineated reaction mechanism also provides experimental evidence for the reversible interconversion between the oft-proposed organogold intermediates obtained in this step of the tandem process.